Modulation of Radiation and Mitomycin C Induced Chromosomal Aberrations by Apigenin in Human Lymphocytes In vitro - Sharma, Narinder K. (Current Overview on Disease and Health Research Vol. 3, 2022)
The objective of this study is to investigate the modulatory effects of Apigenin (APG) on human lymphocytes after irradiation with gamma rays (3 Gy) or treatment with the antineoplastic agent, mitomycin C (MMC), in vitro. Cytogenetic biomarkers such as chromosome aberrations (CAs), sister chromatid exchanges (SCEs), and cytochalasin-B blocked micronuclei (CBMN) were investigated in blood lymphocytes treated with radiation, antineoplastic agent (MMC), and APG. Using a standard protocol, whole blood lymphocytes were grown in vitro. The frequency of CAs or micro-nuclei (MN) in human peripheral blood cells that had undergone gamma radiation (3 Gy) and subsequently been post-treated with APG did not differ significantly from one another. In comparison to controls, the frequency of SCEs per cell was higher in samples treated with APG. In comparison to MMC treatment alone, lymphocytes treated with MMC in the presence of APG showed a significant reduction (P < 0.01) in the frequency of SCEs. The data for the MN test showed that APG treatment significantly reduced (P < 0.01) the frequency of MMC-induced MN.